2017
DOI: 10.1148/radiol.2016160092
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Surgery: Risk of Radiographic Joint Space Narrowing Progression and Subsequent Knee Replacement—Data from the Osteoarthritis Initiative

Abstract: Purpose To investigate the risk of radiographic joint space narrowing (JSN) progression evaluated in subjects with and those without underlying osteoarthritis at baseline and knee replacement (KR) associated with meniscal surgery in subjects with and those without a reported history of preceding knee trauma. Materials and Methods The HIPAA-compliant protocol was approved by the institutional review boards of the participating centers. Written informed consent was obtained from all participants. Subjects who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Treatment can be divided into conservative and surgical management options, depending on a variety of factors, including the shape, size, and location of the meniscus tear, as well as the age and physical activity of the patient [7][8][9][10]. Adequate treatment may reduce sequela of meniscus tears, improve quality of life, and reduce health care costs [11][12][13][14]. Therefore, accurate diagnosis of meniscus tears is important.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment can be divided into conservative and surgical management options, depending on a variety of factors, including the shape, size, and location of the meniscus tear, as well as the age and physical activity of the patient [7][8][9][10]. Adequate treatment may reduce sequela of meniscus tears, improve quality of life, and reduce health care costs [11][12][13][14]. Therefore, accurate diagnosis of meniscus tears is important.…”
Section: Introductionmentioning
confidence: 99%
“…Although more and more randomized trials including patients with symptomatic KOA and meniscal tears found no greater benefit with arthroscopic surgery followed by physical therapy, [30,33] compared with physical therapy alone, our observational study showed high rates of functional improvement, despite of serious radiologic KOA progression within patients after arthroscopic partial meniscectomy and debridement. We believe that meniscus surgery can promote radiologic KOA progression [34] ; however, patient's conscious symptoms and radiological presentations are not completely consistent and even contradictor each other, and some patients were well satisfied with surgical effect while imaging revealed a severe degree of KOA progression. The degree of joint space narrowing does not fully represent the degree of degeneration of the joint.…”
Section: Discussionmentioning
confidence: 99%
“…The fibrocartilaginous meniscus is commonly injured, can lead to accelerated cartilage wear, and is frequently managed surgically with the rise in popularity of meniscus-preserving surgeries. 34,35 MRI remains the noninvasive modality of choice for the diagnosis of meniscal tears that are characterized by abnormal meniscal morphology and/or signal intensity. 36 Diagnostic performance of MRI when interpreted by radiologists in terms of sensitivity and specificity is 93% and 88% for medial meniscus tears and 79% and 96% for the lateral meniscus.…”
Section: Meniscus Meniscus Evaluation: Mrimentioning
confidence: 99%